Investigating the Impacts of Job Stress on the University Librarians within the Persepective of Human Resource Management: The Case of North Cyprus - Dinçyürek, Akman (Social Science Electronic Publishing, Inc., 2010)
Librarians in there relations with there customers and with other librarians have to establish good relations. Librarians work long hours and it is somewhat monotonous. Librarians are also busy with a collateral work while working as a librarian. Working together busy sincere, warm relations among managers and working personnel. University libraries are integral part of every university and they have to meet the demands of students in thousands. The aim of this article is to find out the effects of stress on university librarians working in Northern Cyprus as useful human resources, and propose certain strategies to create a good environment for the librarians to work effectively and with endless determination in their jobs. Also research article about job stress improvements related to business administrative in introduction.
The file in this item is the publisher version (published version) of the article.
Keywords: stress management; librarians; library management; human resources management